IMPROVING ADOLESCENT KNOWLEDGE OF SMOKING HAZARDS - Meli Diana; Sulfatus Zakiya; Intan Nurul Anggriani; Dince Debora Saikmata; Retno Dwi Puspita Sari; Fitria Isnaini Ramadhani; Jannatun Noer Khabibah; Khaidar Rachman; Tri Astutik Wahyu Utami (Community Service Journal of Indonesia, 2019)
Health Promotion Activities about the Dangers of Smoking in Adolescents at MTs Islamiyah Tanggulangin, Sidoarjo is one form of community service in the form of counseling aimed at growing and improving healthy behavior in adolescents, especially in recognizing the dangers of smoking for health. The activity was carried out on November 21, 2018 at MTs Islamiyah Tanggulangin, Sidoarjo. The target is students of MTs Islamiyah Tanggulangin Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for 3 weeks before the activity is carried out, starting from the selection of health counseling materials to the submission of permits to the relevant parties. As an evaluation, the activity was attended by 40 students and 2 teachers, participants participated in the activity with enthusiasm and conducive, the activity can be carried out on time smoothly. Keywords: Adolescent knowledge, smoking hazard, health promotion.